The application of conceptual modelling approach to evaluate the impacts of climate change on the future streamflow in three unregulated catchments of the Australian hydrologic reference stations - Al-Safi, H.I.J.; Sarukkalige, Ranjan (2019)
© 2019 Inderscience Enterprises Ltd. The future climate-change impacts on streamflow variability at three-contributing catchments of the Australian-hydrologic-reference-stations (HRSs), Harvey, Beardy and Goulburn catchments, are presented in this study. Observed hydro-meteorological data from the contributing-catchments were used to calibrate and validate the HBV-hydrological-model before the streamflow prediction. The downscaled future rainfall and temperature from a multi-model ensemble of eight-GCMs of the CMIP5 under two representative-concentration-pathways RCP4.5 and RCP8.5 were used to run the calibrated HBV-model to simulate the future daily streamflow at the three-HRSs. Nearly all GCMs predict reduction-tendencies in annual mean rainfall and an increase in temperature and potential evaporation across the studied catchments during the mid (2046-2065) and late (2080-2099) of the 21st-century. The annual mean streamflow across the three-catchments also tend to decrease during the future periods under the two climate scenarios and ranged between 31-60% for the Harvey-catchment, 1-24% for the Beardy-catchment and 18-42% for the Goulburn-catchment relative to the control-run.